Equivalent damping ratio model of flexure-shear critical RC columns. (1st January 2017) - Zhang, Yan-qing; Gong, Jin-xin; Zhang, Qin; Han, Shi
Highlights: Hysteretic loop expression of flexural-shear critical RC columns under complete cyclic loading is developed. An equivalent damping ratio model suitable for flexural-shear critical RC columns is proposed. A design example of two-column pier supported bridge is provided to illustrate the application of the proposed model. Abstract: To describe the hysteretic behavior of flexure-shear critical reinforced concrete (RC) columns realistically, a hysteretic loop expression of flexure-shear critical RC columns under complete cyclic loading is proposed by investigating the characteristics of column specimens in PEER - Column Database. For the proposed expression, important characteristics of flexure-shear critical RC columns under cyclic loading, including pinching and stiffness degradation, are covered. And then, an equivalent damping ratio model suitable for flexure-shear critical RC columns is proposed by using the proposed hysteretic loop expression based on the Jacobsen's approach. The relationship between the equivalent damping ratio formula of two-column pier supported bridge and that of its columns is developed based on the energy dissipation capacity. A design example is provided to illustrate the application of the proposed model.